Organ donation in India—A social marketing perspective. Issue 2 (8th March 2019) - Mohan, Geetha; Aswathy, Asokan A.
Abstract : Organ donation is a social issue, and marketers face challenges promoting it. If factors aiding and inhibiting it are identified, it becomes easier to enhance intention of donating organs. The objective of this research is to establish the role of perceived awareness, family support, perceived individual value, and religiosity on organ donation intention (ODI). A sample of 247 respondents answered a structured questionnaire. Proposed model is mediated by organ donation attitude (ODA) and moderated by perceived risk. Findings from the study show that all the predictors are positively related with ODI mediated through ODA and perceived risk moderates the influence of ODA on ODI.